Recent advances in the field of non-coding RNAs in cancer - Calin, George; Shah, Maitri (Henry Stewart Talks, 2018)
Types of non-coding RNAs, Role of microRNAs and long non-coding RNAs in cancers, Recent advances in strategies to utilize miRNAs and lncRNAs as biomarkers in cancer, miRNAs and lncRNAs are currently in clinical development as diagnostic, prognostic and predictive biomarkers for cancer, Recent advances in strategies to utilize miRNAs and lncRNAs as therapeutic targets in cancer